Cultural barriers to intercultural/ interracial communication among black and white South African women - Lynn Parry (Communicare)
There are a number of Important cultural barriers between black and white South African women. These Include language, nonverbal communication, world view, thought pat terns and stereotypes. In an attempt to Investigate some of the cultural barriers this exploratory study focuses on the opinions of 20 black South African women and 20 white South African women. A convenience sample was used and the respondents were undergraduate students at the University of South Africa. Personal semi-structured interviews were conducted with the respondents. Open-ended questions were used allowing each respondent to provide her own perspective or point of view.